2007
DOI: 10.1682/jrrd.2006.10.0132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spectral and entropic measures for surface electromyography time series: A pilot study

Abstract: Abstract-In a previous study, we reported that the mean square displacement calculated from the surface electromyography (sEMG) signal of low back muscles exhibits a plateaulike behavior for intermediate times 20 ms < t < 400 ms. This property indicates the existence of correlations in the signal for times much longer than the inverse of the median frequency (MF), which is calculated from the power spectrum 1/ = 1/(100 Hz) = 10 ms, where is the MF. This result suggests the use of methods from nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 29 publications
6
29
1
2
Order By: Relevance
“…Our previous study indicated that control subjects revealed significantly larger entropy levels of the EMG signals than subjects with LBP [3]. Thus, the results of the current study consistently demonstrated a connection between physiological "health" and complexity [4,13].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our previous study indicated that control subjects revealed significantly larger entropy levels of the EMG signals than subjects with LBP [3]. Thus, the results of the current study consistently demonstrated a connection between physiological "health" and complexity [4,13].…”
Section: Discussionsupporting
confidence: 84%
“…This plateau value of S t was referred to as the entropy. The detailed entropy calculation process is fully described in previous studies [1][2][3]. Our previous data were partially used in this study in order to monitor the effects of the exercise intervention.…”
Section: Electromyography Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Ademais, há de se ressaltar que estudos recentes têm indicado que a musculatura lombar possui uma função importante na identificação de grupos lombálgicos (SUNG; ZURCHER; KAUFMAN, 2007;HEYDARI et al, 2010).…”
Section: Teste De Sorensenunclassified